Africans' cultural dilemma - Nkosi, John (International Library of African Music, 1964)
Africans almost invariably prefer Western culture — Western dress, manners, usages and speech — to their own. Western culture is associated with economic advantage as well as with status. But this preference places the African in a dilemma. He has a seemingly desperate choice of becoming a forlorn imitator of the Whites or of retaining his African identity and abandoning all the symbols of progress. It goes without saying that African songs should be preserved and African singing cultivated, especially of the kind that Miss Makeba has made so popular overseas. The handicap here is that singing is apt to have tribal significance and to promote tribal rivalries. To counter this there will have to be built up a sense of inter-tribal pride in the achievements of the great African “stars.”
Keywords: African Music